2006
DOI: 10.1159/000096495
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Bilateral Subthalamic Nucleus Stimulation in Patients with Advanced Parkinson’s Disease

Abstract: Background: In patients with advanced Parkinson’s disease (PD), deep brain stimulation (DBS) of the subthalamic nucleus (STN) has been shown to improve motor function and decrease medication requirements in the short term. However, the long-term benefits of DBS are not yet established. Objective: It was the aim of this study to evaluate long-term outcomes of patients with PD treated with bilateral DBS of the STN. Design and Methods: Thirty-three subjects who had bilateral STN DBS were followed prospectively af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 35 publications
(23 reference statements)
5
31
0
Order By: Relevance
“…Stimulation seemed to improve some aspects of pharyngeal swallowing while the oral stage was unaffected (22). In other reports, the effects of DBS surgery on swallowing functionality varies from unchanged (23,24), to a clear-cut deterioration (25). Dysphagia has further been reported as a rare complication after STN DBS, which in some of the cases was clearly related to the stimulation (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 89%
“…Stimulation seemed to improve some aspects of pharyngeal swallowing while the oral stage was unaffected (22). In other reports, the effects of DBS surgery on swallowing functionality varies from unchanged (23,24), to a clear-cut deterioration (25). Dysphagia has further been reported as a rare complication after STN DBS, which in some of the cases was clearly related to the stimulation (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 89%
“…[112][113][114][115][116] An equally common finding in these long term studies, however, is worsening gait function. One recent study, for example, reported 10-year outcomes of bilateral STN DBS in PD.…”
Section: Deep Brain Stimulation For Pd -Long-term Studies On Gait Andmentioning
confidence: 97%
“…Many studies have shown stable improvement in patients' UDPRS scores after bilateral STN DBS (Krack et al, 2003;Liang et al, 2006;Ostergaard & Sunde., 2006;Piboolnurak et al, 2007;Wider et al, 2008;Tsai et al, 2009), although the scores were observed to diminish over time due to disease progression (Olanow et al, 1995;Louis et al, 1999;Jankovic et al, 2001;Krack et al, www.intechopen.com Rodriguez-Oroz et al, 2005;Tsai et al, 2009). In a review of the literature, Benabid et al (2009) found that improvements in UDPRS III scores after STN DBS were reasonably stable over time, decreasing from 66% improvement at one year to 54% improvement five years after surgery (Benabid et al, 2009).…”
Section: Three-year Long-term Outcome Following Bilateral Stn Dbs Witmentioning
confidence: 99%